Characterization of the mitochondrial genomes for Ophiostoma ips and related taxa from various geographic origins and related species: large intron-rich genomes and complex intron arrangements - Jigeesha Mukhopadhyay; Alvan Wai; B. Franz Lang; Georg Hausner (IMA Fungus)
The Ophiostomatales are of economic concern, as many are blue-stain fungi and some are plant pathogens. The mitogenomes of members assigned to this order exhibit size polymorphism despite having highly conserved gene order, owing to the variable number of introns and intron insertion sites. In this work, eleven blue-stain fungi, including nine strains of Ophiostoma ips with a varied distribution across North America and New Zealand, were sequenced and compared with other members of the Ophiostomatales. A pan-mitogenome intron landscape has been prepared to demonstrate the distribution of the mobile genetic elements and to provide insight into the evolutionary dynamics of introns among members of this group of fungi. The size variation among these mitogenomes (from about 23.8 kb to 152 kb) shows high correlation to the presence and absence of introns. Examples of complex or nested introns composed of two or three intron modules have been observed in some O. ips strains. RNA-seq data suggests possible splicing pathways with regard to resolving these complex introns. Mitochondrial DNA and RNA data for O. ips provides the basis for future studies relating to gene annotation, alternative splicing, evolutionary intron dynamics, and taxonomic investigations for members of the Ophiostomatales.